ANALISIS KEBUTUHAN DAYCARE UNTUK ANAK BURUH DI KAWASAN BERIKAT NUSANTARA CAKUNG - Handayani, Penny; Kristiani, Reneta; Kawatu, Florentina Resa; Sembiring, Weny Pandia; Sutarno, Herman Josep (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
The protection and fulfillment of children's rights are the responsibility of the father and mother. However, for parents who work as laborers, this is difficult to do because of long working hours, working shift systems, heavy workloads, dual role conflicts of women workers, economic pressure, weak social support from extended families, and family conflicts. APSAI, ISBS, LPM-UAJ, and the Workers Union Organization built a collaboration to provide quality daycare services for child workers in industrial areas. The Cakung Bonded Zone (KBN) was chosen as the pilot project. KBN Cakung was chosen as an area where it is important to have daycare facilities because the majority of workers are women. Based on the results of this study, it is hoped that the need for daycare establishment at KBN Cakung can be identified. It is hoped that KBN Cakung will become the first industrial area to support efforts to fulfill children's rights with quality through a daycare in industrial areas. The data collection design used was a mixed-method (quantitative and qualitative) to produce a broader understanding of the needs and patterns of early childhood care in KBN, Cakung. Questionnaire and FGD guide instruments were used to identify the context of patterns and needs of early childhood care for workers in KBN. Based on the results of the needs mapping of 12 child participants in the target age range of beneficiaries, 11 parents who work in factories and 11 parents who do not work in the factory but live around KBN Cakung, the following results are obtained: (1) There is a need for the availability of child care service facilities. early, but facilities are not yet available, (2) Parents care about child caregivers and are ready to contribute a maximum of IDR 500,000 per month (including food), (3) Potential beneficiary children want a safe, spacious, simple environment, and caregivers that can make children comfortable and can be invited to play, (4) The necessary care for children is what can make children: smart, healthy, safe and independent. Perlindungan dan pemenuhan hak anak menjadi tanggung jawab ayah dan ibu. Namun pada orangtua yang berprofesi sebagai buruh, hal ini sulit dilakukan karena jam kerja yang panjang, bekerja dengan sistem shift, beban kerja yang berat, konflik peran ganda buruh perempuan, tekanan ekonomi, lemahnya dukungan sosial dari keluarga besar, serta konflik keluarga. APSAI, ISBS, LPM-UAJ, dan Organisasi Serikat Pekerja membangun kerjasama untuk menyediakan layanan daycare berkualitas bagi anak-anak pekerja di kawasan industri. Kawasan Berikat Nusantara (KBN) Cakung dipilih sebagai pilot project. KBN Cakung terpilih sebagai kawasan yang penting memiliki fasilitas daycare adalah jumlah pekerja yang mayoritas perempuan. Berdasarkan hasil kajian ini diharapkan dapat diketahui kebutuhan pendirian daycare di KBN Cakung. Diharapkan KBN Cakung menjadi kawasan industri yang pertama mendukung upaya pemenuhan hak anak yang berkualitas dengan adanya daycare di kawasan industri. Desain pengambilan data yang digunakan adalah mixed method (kuantitatif dan kualitatif) untuk menghasilkan pemahaman yang lebih luas tentang kebutuhan dan pola pengasuhan anak usia dini di KBN, Cakung. Instrumen kuesioner dan panduan FGD digunakan untuk mengidentifikasi konteks pola dan kebutuhan pengasuhan pada anak usia dini pada pekerja di KBN. Berdasarkan hasil pemetaan kebutuhan terhadap 12 partisipan anak rentang usia target penerima manfaat, 11 orangtua yang bekerja di pabrik dan 11 orangtua yang tidak bekerja di pabrik namun tinggal di sekitar KBN Cakung, didapatkan hasil sbb: (1) Ada kebutuhan tersedianya fasilitas layanan penitipan anak usia dini, tetapi fasilitas belum tersedia, (2) Orangtua peduli dengan pengasuh anak dan siap berkontribusi maksimum Rp 500.000 per bulan (sudah termasuk makanan), (3) Anak-anak calon penerima manfaat ingin ada lingkungan yang aman, luas, sederhana, dan pengasuh yang dapat membuat nyaman serta bisa diajak bermain, (4) Pengasuhan anak yang dibutuhkan adalah yang dapat membuat anak : pintar, sehat, aman dan mandiri.